Different Gene Expression Patterns between Leaves and Flowers in Lonicera japonica Revealed by Transcriptome Analysis - Zhang, Libin; Long, Yan; Fu, Chunhua; Xiang, Jun; Gan, Jianping; Wu, Gang; Jia, Haibo; Yu, Longjiang; Li, Maoteng (Frontiers in Plant Science, 2016)
The perennial and evergreen twining vine, Lonicera japonica is an important herbal medicine with great economic value. However, gene expression information for flowers and leaves of L. japonica remains elusive, which greatly impedes functional genomics research on this species. In this study, transcriptome profiles from leaves and flowers of L. japonica were examined using next-generation sequencing technology. A total of 239.41 million clean reads were used for de novo assembly with Trinity software, which generated 150,523 unigenes with N50 containing 947 bp. All the unigenes were annotated using Nr, SwissProt, COGs (Clusters of Orthologous Groups), GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) databases. A total of 35,327 differentially expressed genes (DEGs, P≤0.05) between leaves and flowers were detected. Among them, a total of 6,602 DEGs were assigned with important biological processes including “Metabolic process”, “Response to stimulus”, “Cellular process” and etc. KEGG analysis showed that three possible enzymes involved in the biosynthesis of chlorogenic acid were up-regulated in flowers. Furthermore, the TF-based regulation network in L. japonica identified three differentially expressed transcription factors between leaves and flowers, suggesting distinct regulatory roles in L. japonica. Taken together, this study has provided a global picture of differential gene expression patterns between leaves and flowers in L japonica, providing a useful genomic resource that can also be used for functional genomics research on L. japonica in the future.